PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP N 14 SAROLANGUN - Jelita Rahman; Ade Susanti; Awatif (Mat-Edukasia, 2022)
Learning style is one of the factors that influence learning outcomes. In this case it can be seen from the learning styles of students who take part in mathematics learning, when the teacher explains the lesson, many students' behavior shows different learning styles, there are students who pay attention, there are students who are busy taking notes, and there are students who like to chat with friends. seat without paying attention to the teacher's explanation. The purpose of this study was to determine and describe the significant influence between learning styles on mathematics learning outcomes. This study uses a quantitative approach with the method used is correlation. The population and sample in this study were all seventgrade students of SMP N 14 Sarolangun in the 2020/2021 academic year with a total of 50 students. The sampling technique in this research is total sampling. Data for learning style variables were obtained by distributing student learning style questionnaires. While the learning outcomes obtained from mathematics subject teachers. The data analysis technique used to test the hypothesis is the person product moment correlation, to test the significance using the Z-test, followed by the coefficient of determination formula to state the size of the contribution of the X variable to the Y variable. Then, a simple linear regression test and a regression significance test were carried out. Based on data analysis shows that ≥ or 74.273 > 0.279 then is rejected and is accepted, meaning that there is a significant influence between learning styles on mathematics learning outcomes for class VII SMP N 14 Sarolangun in the academic year 2020/2021, with a contribution of 60,684% and the remaining 39,316 % influenced by other factors